On rate of convergence of Fourier series of a function of WienerÂ´s class - Siddiqi, R. (Revista Técnica da Faculdade de Engenharia da de Zulia)
The main object of this paper is to obtain the rate of convergence of Fourier series of a function of Wiener’s class. From our theorem we can deduce a generalized version of a theorem of Wiener.